2009
DOI: 10.1002/fuce.200900023
|View full text |Cite
|
Sign up to set email alerts
|

Power Generation and Electrochemical Analysis of Biocathode Microbial Fuel Cell Using Graphite Fibre Brush as Cathode Material

Abstract: To improve cathodic efficiency and sustainability of microbial fuel cell (MFC), graphite fibre brush (GFB) was examined as cathode material for power production in biocatalysed‐cathode MFC. Following 133‐h mixed culturing of electricity‐producing bacteria, the MFC could generate a reproducible voltage of 0.4 V at external resistance (REX) of 100 Ω. Maximum volumetric power density of 68.4 W m–3 was obtained at a current density of 178.6 A m–3. Upon aerobic inoculation of electrochemically active bacteria, char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 43 publications
2
31
0
1
Order By: Relevance
“…Power densities of 24.7 and 68.4 W m −3 were achieved with biocathodes based on graphite fiber brushes [35,39]. Differences in power densities can be attributed to the operation conditions, MFC design and cathode surface area.…”
Section: Discussionmentioning
confidence: 99%
“…Power densities of 24.7 and 68.4 W m −3 were achieved with biocathodes based on graphite fiber brushes [35,39]. Differences in power densities can be attributed to the operation conditions, MFC design and cathode surface area.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of a wet air cathode inoculated with a consortium of sludge and sediment microbes was increased through the interactions of the microorganisms on the cathode surface [131,139]. The use of a biocathodes has also been reported to reduce charge transfer resistance of the cathode from 188 to 17 ohms [140] and 40.2 to 12 ohms [141]. Microbial community analysis of the biocathode has identified a wide range of organisms present in the anode community including representatives of the divisions: Betaproteobacteria, Bacteroidetes, Alphaproteobacteria, Chlorobi, Deltaproteobacteria, Actinobacteria, and Gammaproteobacteria [141].…”
Section: Cathode Interactionsmentioning
confidence: 99%
“…Synthetic membranes include anion exchange membranes, cation exchange membranes and ultra filtration membranes. Studies have shown that anion exchange membranes perform better than cation exchange membranes due to a lower resistance (You et al, 2009) . These types of membranes are generally very expensive, have high minimum orders or incur large freight charges as they are only manufactured overseas.…”
Section: Membranementioning
confidence: 99%
“…The platinum acts as a catalyst and is necessary to enhance the rate of reduction of oxygen at the cathode . As platinum is highly expensive and can be poisoned by components of the substrate solution You et al, 2009) www.intechopen.com it is desirable to eliminate it from MFCs and MECs altogether. Several alternatives have been investigated including chemical catholytes, biocathodes and transitional metals (He & Angenent, 2006).…”
mentioning
confidence: 99%